Coral Reef Restoration Handbook - Precht, William (CRC Press, 2009)
"… this book is the first to describe, in detail, the art and science of coral reef restoration. It is to be hoped that the information that can be gleaned within the pages of this book will set a path towards continued preservation of this valuable underwater treasure to be used, appreciated, and experienced for future generations." -- Senator Bob Graham (retired), Miami Lakes, Florida, from the Foreword